(untitled) (Asian Journal of Medical and Biological Research, 2015)
Seasonal variation of water quality parameters and health condition of some small endangered open water fishes are Baila (Glossogobius giuris), Gutum (Lepidocephalichthys guntea) and Tara baim (Macrognathus aculeatus) was carried out through clinical and histological observation from Kailla beel of Ishargonj upazila, Mymensingh and Surma river, Gobindogonj upazila, Sunamgonj district, Sylhet region for a period of eight months from September 2014 to April 2015. Water quality parameters like water temperature, dissolved oxygen, pH, ammonia, alkalinity, hardness, and nitrate were recorded. Water temperature, pH, alkalinity and hardness were found at unfavorable level for fish in mid November and January. Clinical examinations of the fish were carried out at monthly intervals and any kind of abnormalities were recorded. Clinically it was observed that, fish was affected with fin and tail rot, gill rot, parasitic infestation, nutritional deformities, numerous red spots and patches in lateral and ventral regions, large deep whitish ulcers reached up to deep ulcers especially in December and January in both region. Samples of skin, muscle, gill, liver and kidney were collected and processed for histological observations. Major pathology in the skin and muscle were epidermis separated from dermis, presence of fungal granuloma, vacuums, hemorrhage and necrosis. Loss of primary and secondary gill lamellae, hypertrophy and primary gill lamellae separated, necrosis and hemorrhage were found in the gill. Large vacuums, necrosis and hemorrhage were observed in liver and kidney. Among the affected fish organs skin and muscle, gills were more affected than the internal organs like liver and kidney. Overall, clinical and histological observations of fishes were found to be more affected in December and January. Whereas, in the months of mid February to April, the pathological condition of fish gradually healed up to normal except few vacuums and hemorrhage. Under histopathological observations, fishes of Kailla beel were more affected than the fishes of surma river. In clinical and histopathological observation open water fishes were more susceptible due to EUS. Asian J. Med. Biol. Res. June 2015, 1(1): 95-102